(x+4)(2x+2)=

Simple and best practice solution for (x+4)(2x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)(2x+2)= equation:


Simplifying
(x + 4)(2x + 2) = 0

Reorder the terms:
(4 + x)(2x + 2) = 0

Reorder the terms:
(4 + x)(2 + 2x) = 0

Multiply (4 + x) * (2 + 2x)
(4(2 + 2x) + x(2 + 2x)) = 0
((2 * 4 + 2x * 4) + x(2 + 2x)) = 0
((8 + 8x) + x(2 + 2x)) = 0
(8 + 8x + (2 * x + 2x * x)) = 0
(8 + 8x + (2x + 2x2)) = 0

Combine like terms: 8x + 2x = 10x
(8 + 10x + 2x2) = 0

Solving
8 + 10x + 2x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(4 + 5x + x2) = 0

Factor a trinomial.
2((4 + x)(1 + x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Solution

x = {-4, -1}

See similar equations:

| x^2-2x+400=0 | | 25=5+.50x | | (q-3)*2=16 | | 12x-31=38+9x | | 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x | | 79x^2-200x+125=0 | | x+7+3x=13+x | | 6(a-3)= | | 45-33x+33-44x=-45+33x-33+44x | | 11x-11=7x+12 | | 4j+4=6 | | 6y-5=3+4y | | 3x^2y^4+7x^2y^4-10x^4y^2= | | 3k+5-k=-9 | | -2x=160 | | 2((x-2)/2)=0 | | 2((x-2)/2) | | 45-33x+33-44=-45+33x-33+44x | | 3y-3=14 | | -7x-3+6x=-8x+9 | | 12x+18y=50 | | -10x+10x-10x= | | 7a+5(a-3)= |

Equations solver categories